2003
DOI: 10.1140/epjc/s2003-01309-y
|View full text |Cite
|
Sign up to set email alerts
|

Deformed field theory on $\kappa$ -spacetime

Abstract: A general formalism is developed that allows the construction of a field theory on quantum spaces which are deformations of ordinary spacetime. The symmetry group of spacetime (Poincaré group) is replaced by a quantum group. This formalism is demonstrated for the κ-deformed Poincaré algebra and its quantum space. The algebraic setting is mapped to the algebra of functions of commuting variables with a suitable ⋆-product. Fields are elements of this function algebra. The Dirac and Klein-Gordon equation are defi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
229
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(241 citation statements)
references
References 31 publications
3
229
1
Order By: Relevance
“…Furthermore it has been shown that the space-times associated with a variety of black holes at the Planck scale could be described by a κ-Minkowski algebra [16][17][18]. In this paper we shall take the κ-Minkowski algebra [19][20][21][22][23][24][25][26][27][28] as the prototype of a space-time at the Planck scale and shall investigate various features of QNM's and associated physics in that background.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore it has been shown that the space-times associated with a variety of black holes at the Planck scale could be described by a κ-Minkowski algebra [16][17][18]. In this paper we shall take the κ-Minkowski algebra [19][20][21][22][23][24][25][26][27][28] as the prototype of a space-time at the Planck scale and shall investigate various features of QNM's and associated physics in that background.…”
Section: Introductionmentioning
confidence: 99%
“…When noncommutativity is present Lorentz symmetry is usually broken, but recent results suggest that for some special choices of the tensors θ and ρ Lorentz symmetry might be deformed, in the sense of the recently proposed "doublyspecial relativity" scenario [53], rather than broken. In particular, this appears to be the case for the Lie-algebra κ-Minkowski [54,55,58,71,72,73] noncommutative spacetime (l, m = 1, 2, 3)…”
Section: Modified Dispersion Relations In κ-Minkowski Noncommutative mentioning
confidence: 93%
“…Such spaces are believed to be important for the understanding of quantum gravity. Recent realizations of noncommutativity in such contexts have been described for κ-Minkowski space [1] and in doubly special relativity [2], among many others.…”
Section: Noncommutative Spacesmentioning
confidence: 99%